2019
DOI: 10.1002/jrs.5766
|View full text |Cite
|
Sign up to set email alerts
|

Strain engineering of the lattice vibration modes in monolayer black phosphorus

Abstract: Strain engineering can be served as an efficient tool for tuning physical properties of two‐dimentional (2D) materials. However, the quantifying strain and characterizing its spatially inhomogeneous distribution are always challenging. Here, we report the strain‐induced lattice vibration mode variations in monolayer black phosphorus (BP) and clarify the underlying mechanism resorting to the bond relaxation theory based on the combination of mass‐spring model and Lagrangian dynamics. We reveal that the Ag2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…2), suggesting the dynamic stability, which agrees with the theoretical results obtained by other groups. 16,21,25 The highest frequency of the phonon for GeP 3 (InP 3 ) is 448 cm À1 (452 cm À1 ), which is comparable to black phosphorene 51,52 and can be attributed to the apparent mechanical robustness of the covalent P-P bonds.…”
Section: Resultsmentioning
confidence: 98%
“…2), suggesting the dynamic stability, which agrees with the theoretical results obtained by other groups. 16,21,25 The highest frequency of the phonon for GeP 3 (InP 3 ) is 448 cm À1 (452 cm À1 ), which is comparable to black phosphorene 51,52 and can be attributed to the apparent mechanical robustness of the covalent P-P bonds.…”
Section: Resultsmentioning
confidence: 98%
“…Similar anisotropic behavior in the vibrational spectrum was observed for BP. 54 It was reported that three Raman-active modes (A g 2 , B 2g , and A g 2 ) of BP display red shift for A g 2 mode and blue shift for B 2g and A g 2 in the armchair direction under compressive strain. Conversely, A g 2 shifts blue, and B 2g and A g 2 modes shift red in tension.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…However, little is known about the mechanical responses of 2D β-TeO 2 . Given that mechanical deformation also affects the lattice vibrational modes, Raman spectroscopy, as a non-destructive characterization technique, can extract valuable information about the strain state of a material, aiding the study of NPR in 2D materials [17,18].…”
Section: Introductionmentioning
confidence: 99%